Parasites of the hermit crab Pagurus hirsutiusculus; distribution, prevalence, and thermal ecology - Madeleine H. Abbott; Christopher D.G. Harley; Harmony A. Martell; Carly Janusson; Matthew A. Lemay; Alyssa-Lois M. Gehman (PLoS ONE, 2025)
Parasites are common throughout the biosphere and can play significant ecological roles. However, most parasites are understudied, particularly with regards to how their prevalence and impacts vary with environmental conditions. As a result, there remains an incomplete understanding of how both parasites and their hosts may be impacted by climate change. We conducted field surveys to better understand the parasite distributions of the intertidal hermit crab Pagurus hirsutiusculus in British Columbia . We found three genera of externally visible parasites ( Eremitione giardi, Peltogasterella sp., and Peltogaster sp.), and one hyperparasite ( Liriopsis pygmaea ), which were present throughout the surveyed region. The prevalence of E. giardi was related to salinity while Peltogaster sp. was related to host size. At some locations, we observed a decline in prevalence in the parasite Peltogaster sp. following the 2021 Pacific Northwest heat wave event. In the lab, we compared the metabolic rate across a temperature range and survivorship post heat stress in individuals infected with Peltogaster sp. and uninfected individuals. We did not find a difference in metabolism based on infection status but found that uninfected individuals had significantly higher survivorship following heat stress. This study highlights the pervasiveness of parasitic interactions and demonstrates the need to study them in combination with environmental factors to better understand the effects of climate change on populations.